β-alanine: A Comprehensive Review of Athletic and Systemic Benefits - Stanibuła, Dominik; Redner, Aneta; Rybowski, Jakub; Popiel , Michał; Smala, Kamila; Dziekoński , Kamil; Zwierzchlewska, Patrycja; Głowacz, Julia; Kulig, Klaudia; Wiśniowski, Maksymilian (Quality in Sport, 2025)
Purpose: This paper aims to critically review the latest research on β‐alanine supplementation, examining its impact on muscle performance, endurance, and overall athletic output. In addition, the study explores the supplement’s systemic effects - including metabolic regulation and cognitive function - while addressing optimal dosing strategies and potential health risks. Methodology: A comprehensive literature review was conducted using multiple scientific databases, including PubMed, Scopus, and Google Scholar. The selection criteria prioritized clinical trials, systematic reviews, and meta-analyses that investigated the effects of β‐alanine on muscular function, metabolic parameters, and cognitive outcomes. Studies were evaluated for their methodological rigor, relevance, and practical applications, with special attention given to the mechanisms underlying β‐alanine’s role in increasing muscle carnosine levels and mitigating exercise-induced fatigue. Findings: The review found that β‐alanine supplementation effectively elevates muscle carnosine levels, enhancing the muscle’s buffering capacity against acid accumulation during high-intensity exercise. This biochemical improvement is associated with delayed onset of fatigue and enhanced performance in short-duration, high-intensity activities. Additionally, emerging evidence suggests that β‐alanine may offer ancillary benefits, such as improved glucose regulation, reduced oxidative stress, and potential cognitive enhancements under stressful conditions. Conclusions: β‐alanine supplementation represents a promising ergogenic aid for athletes, with multifaceted benefits that extend beyond muscle performance to include metabolic and cognitive health. Current research supports its efficacy in improving anaerobic performance and delaying fatigue. These insights can guide athletes, trainers, and healthcare professionals in the strategic integration of β‐alanine into performance and recovery regimens.